Retinal oximetry in branch retinal vein occlusion. Issue 6 (28th February 2019) - Osaka, Rie; Nakano, Yuki; Takasago, Yukari; Fujita, Tomoyoshi; Yamashita, Ayana; Shiragami, Chieko; Muraoka, Yuki; Tsujikawa, Akitaka
Abstract: Purpose: To measure retinal oxygen saturation (SO2 ) in eyes with branch retinal vein occlusion (BRVO). Methods: Retinal oximetry was performed using the Oxymap T1 retinal oximeter in 50 eyes (50 patients) with resolved BRVO. SO2 was calculated in each major retinal artery and vein in four quadrants. The superior or inferior hemisphere with BRVO was categorized as the affected hemisphere and the other as the unaffected hemisphere. Results: Oxymap T1 allowed us to measure SO2 in major retinal vessels. Both arterial and venous SO2 in the affected hemisphere were significantly higher than those in the unaffected hemisphere. However, there was no significant difference in arteriovenous (A‐V) difference in SO2 between the affected and unaffected hemispheres. Of the 50 included eyes, 32 had non‐ischemic BRVO and 18 had ischemic BRVO. In the affected hemisphere, arterial SO2 was significantly higher in ischemic BRVO (106.9 ± 8.8%) than in non‐ischemic BRVO (101.3 ± 9.2%, p = 0.044). There were no significant differences in venous SO2 between non‐ischemic and ischemic BRVO. Consequently, the A‐V difference in SO2 was significantly higher in ischemic BRVO (51.9 ± 13.9%) than in non‐ischemic BRVO (43.4 ± 11.5%, p = 0.028). In multiple regression analysis, the type of perfusion (non‐ischemic or ischemic) had associations with arterial SO2 ( β = 0 .365, p = 0.013) and with A‐V differences in SO2 in the affected hemisphere ( β = 0 .406, p = 0.006). Conclusion: In ischemic BRVO, arterial SO2 and the A‐V difference in SO2 in the affected hemisphere were significantly higher than in non‐ischemic BRVO.